Studi Kualitas Minyak Goreng Dengan Parameter Viskositas Dan Indeks Bias - Sutiah, Sutiah; Firdausi, K. Sofjan; Setia Budi, Wahyu (BERKALA FISIKA, 2008)
The aim of this research to investigate the quality of palm oil through its viscosity and refractive index before and after used. Viscosimeter Ostwald is used to measure the viscosity and refractive method in prism is used to measure refractive index. The measurement was carried out in room temperature. The samples are fresh oil, and expired oil. Analysis of the quality of palm oil based on viscosity measurement and refractive index show that palm oil that had not been used is the highest value and the palm oil that twice used is the lowest value. Keyword: viscosity, quality of oil